2023
DOI: 10.3390/vetsci10080513
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of GS-441524, Teriflunomide, Ruxolitinib, Molnupiravir, Ritonavir, and Nirmatrelvir for In Vitro Antiviral Activity against Feline Infectious Peritonitis Virus

Abstract: Feline infectious peritonitis (FIP), caused by feline coronavirus (FcoV), is considered one of the most enigmatic diseases in cats. Developing effective drugs for FIP is crucial due to its global prevalence and severity. In this study, six antiviral drugs were tested for their cytotoxicity, cell viability, and antiviral efficacies in Crandell-Reese feline kidney cells. A cytotoxicity assay demonstrated that these drugs were safe to be used with essentially no cytotoxicity with concentrations as high as 250 µM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As we observed no severe damage in HAEs infected with SARS-CoV-2, we could confirm that ruxolitinib effectively inhibited the ISG expression. Although we did not evaluate the cytotoxic concentrations of both inhibitors in HAEs, concentrations of at least 5 µM of ruxolitinib and 6 µM of BX795 were not shown to cause any cytotoxicity in various cell lines, including human airway cells [51][52][53][54][55][56]. For instance, nasal HAEs have been exposed to 10 µM of ruxolitinib [50] and 6 µM of BX795 [4,22,23] without any cytotoxicity being noted.…”
Section: Discussionmentioning
confidence: 99%
“…As we observed no severe damage in HAEs infected with SARS-CoV-2, we could confirm that ruxolitinib effectively inhibited the ISG expression. Although we did not evaluate the cytotoxic concentrations of both inhibitors in HAEs, concentrations of at least 5 µM of ruxolitinib and 6 µM of BX795 were not shown to cause any cytotoxicity in various cell lines, including human airway cells [51][52][53][54][55][56]. For instance, nasal HAEs have been exposed to 10 µM of ruxolitinib [50] and 6 µM of BX795 [4,22,23] without any cytotoxicity being noted.…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral drugs like GS-441524 and remdesivir have been investigated for their efficacy against FIPV, and GS-441524 has shown promising results in reducing viral replication (Barua et al, 2023). This highlights the potential for reevaluating current antiviral agents for FIPV management.…”
Section: Introductionmentioning
confidence: 99%
“…Teriflunomide, a dihydrowhey acid dehydrogenase inhibitor, is an FDA-approved immunomodulator with low cytotoxicity, and used to treat relapse-remission multiple sclerosis in the clinic ( Wiese et al., 2013 ; Scott, 2019 ; Barua et al., 2023 ; Lang et al., 2023 ). Up to now, no study on the antifungal activity of teriflunomide has so far been reported.…”
Section: Introductionmentioning
confidence: 99%